A sustainable forest future - Pearce, D.; Putz, F.E.; Vanclay, J.K. (University of East Anglia, 1999)
Available literature is reviewed to determine the type of forest management best suited to slowing the rate of loss of the world's forests and biodiversity. The traditional argument that sustainable forestry is the most preferred option has recently come under criticism from those who argue that it is neither profitable nor necessarily environmentally preferable to conventional logging. The paper proceeds from comparing financial rates of return to differing forest management systems, through to economic rates of return, and from there to wider rate of return concepts that include non-market values, eg. biodiversity conservation and carbon storage. While sustainable systems appear capable of earning returns in excess of some modest discount rates, eg. 5-10 percent, they do not compete financially with other systems. No other factors appear to give sustainable timber management any edge over conventional systems. If the focus is on sustainable and unsustainable forest systems in developing countries, then high discount rates reinforce the initial preference for conventional systems based on the rapid liquidation of the timber and other resources without regard for future harvests or other impacts. Studies suggest non-market benefits of sustainable systems are significant. Timber yields are less on a comparative basis but non-timber values more than offset the relatively lower yield. The role of carbon is highlighted because carbon values dominate the non-market values overall. An analysis made in the context of a modified forest model, developed by Hyde, suggests the prospect for sustainable forest management is low in the early stages of development, and increases as the values attached to the forest and the services rise over time. Extended to include carbon and biodiversity values, it is arguable that the potential for sustainable forestry is far greater, even in the early stages of development, than might be thought.